PREVALENCE OF HELMINTH PARASITES INFECTING DOMESTIC PIGEONS (COLUMBA LIVIA DOMESTICA) FROM AL-QASSIM REGION, SAUDI ARABIA - Mashael A. Aldamigh; Ahlam A. Alahmadi; Amaal H. Hassan (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
This study aimed to identify helminth parasites infecting domestic pigeons in Al- Qassim region, Saudi Arabia, and the biological factors possibly affecting the prevalence of infection. A total of 354 pigeons (C. L. domestica) were purchased from four cities in Al-Qassim region; Buraydah, Unaizah, Ar Rass, and Al-Bukairiyah, from January to December 2021. Pigeons were examined to determine the helminths prevalence, and the relationship between the infection and the biological factors; city, season, gender, age, and weight. Overall, our study showed 177 (50%) pigeons were infected with helminth parasites. More precisely, 31.6% of pigeons were infected with cestodes, 13.3% with nematodes, and 5.1% with mixed infection (both cestodes and nematodes). No trematodes were recorded in this study.  Cestodes were more common and abundant than nematodes. The correlation between the type of infection and the five biological factors revealed that Buraydah city had a significantly lower rate of cestode infection compared to other cities, while nematode infection was significantly different among the four different seasons. There was no significant difference between the gender factor and a single infection of cestode or nematode, but it had a significant role in mixed infection, this may be due to the fact the sample size was relatively smaller and may be related to males' sex hormones. To our knowledge, this is the first study to shed light on helminths infection in domestic pigeons from Al-Qassim region, Saudi Arabia. This research could aid authorities in taking necessary and preventative measures against pigeon parasitic diseases.